2018
DOI: 10.1021/acs.jafc.8b01686
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds of Kimchi Inhibit Apoptosis by Attenuating Endoplasmic Reticulum Stress in the Brain of Amyloid β-Injected Mice

Abstract: This study investigated the inhibitory effects of kimchi bioactive compounds against endoplasmic reticulum (ER) stress-induced apoptosis in amyloid beta (Aβ)-injected mice. Mice received a single intracerebroventricular injection of Aβ, except for the normal group. Mice were subjected to oral administration of 10 mg of capsaicin, 50 mg of 3-(4'-hydroxyl-3',5'-dimethoxyphenyl)propionic acid (HDMPPA), 50 mg of quercetin, 50 mg of ascorbic acid, or 200 mg of kimchi methanol extract (KME) per kilogram of body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…However, the behavioral task test results from our current study do not correlate with the in vitro P e value. Despite capsaicin having the highest P e value [ 24 ] among the tested compounds, it showed no neuroprotective effects in the AD mice in this study. The possible explanation could be the low dosage (10 mg/kg bw/day) of capsaicin administered to the mice to avoid lethal toxicity.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…However, the behavioral task test results from our current study do not correlate with the in vitro P e value. Despite capsaicin having the highest P e value [ 24 ] among the tested compounds, it showed no neuroprotective effects in the AD mice in this study. The possible explanation could be the low dosage (10 mg/kg bw/day) of capsaicin administered to the mice to avoid lethal toxicity.…”
Section: Discussionmentioning
confidence: 70%
“…ROS and peroxynitrite generation and TBARS production were reduced with a concomitant increase of the GSH level and Nrf2-regulated antioxidant enzymes. Moreover, we had previously observed that treatment of Aβ 25-35 -injected mice with KME or kimchi bioactive compounds reduced the levels of amyloid precursor protein (APP), beta-secretase (BACE), and tau proteins in the brain [ 24 ]. Blood–brain barrier (BBB) penetration of the natural products is a primary requirement for their ability to protect against degenerative neural diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrients originating from Kimchi and its ingredients modulate the Nrf2/PERK signalling pathway to homeostasis in oxidative stress states. Kimchi and its bioactive compound ((3–4′‐hydroxyl‐3′,5′‐dimethoxyphenyl) propionic acid: HDMPPA), which is a metabolite result from fermentation, alleviate oxidative stress and inflammatory response not only via the Nrf2 pathway, but also via the PERK/CHOP pathway, which induced apoptosis of ER, in cardiovascular disease and ageing models [100–102 ]. In addition, Arvelexin from Brassica rapa and anthocyanin‐rich extract from red cabbage exert anti‐inflammatory properties by the inhibition of NF‐ κB activation and by Nrf2‐regulated HO‐1 induction in macrophages and apolipoprotein E‐deficient mice [103, 104 ], suggesting that Nrf2 activation during inflammation antagonizes the NF‐κB pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the capsaicin diet did not reduce tau hyperphosphorylation in healthy rats not affected by type2 diabetes, indicating that dietary capsaicin might prevent AD in individuals affected by type2 diabetes. Capsaicin, present as bioactive compound in Kimchi, a traditional Korean fermented vegetable, also had a tendency to decrease phosphorylated tau proteins in the brain of Aβ-injected mice 97 . In this study protein expression of APP and BACE1, elevated by Aβ injection, also tended to decrease by oral administration of 10 mg capsaicin.…”
Section: Discussionmentioning
confidence: 98%